Two Liters a Day Keep the Doctor Away? Considerations on the Pathophysiology of Suboptimal Fluid Intake in the Common Population - Florian Lang; Isabelle Guelinckx; Guillaume Lemetais; Olle Melander (Karger Publishers, 2017)
Suboptimal fluid intake may require enhanced release of antidiuretic hormone (ADH) or vasopressin for the maintenance of adequate hydration. Enhanced copeptin levels (reflecting enhanced vasopressin levels) in 25% of the common population are associated with enhanced risk of metabolic syndrome with abdominal obesity, type 2 diabetes, hypertension, coronary artery disease, heart failure, vascular dementia, cognitive impairment, microalbuminuria, chronic kidney disease, inflammatory bowel disease, cancer, and premature mortality. Vasopressin stimulates the release of glucocorticoids which in turn up-regulate the serum- and glucocorticoid-inducible kinase 1 (SGK1). Moreover, dehydration upregulates the transcription factor NFAT5, which in turn stimulates SGK1 expression. SGK1 is activated by insulin, growth factors and oxidative stress via phosphatidylinositide-3-kinase, 3-phosphoinositide-dependent kinase PDK1 and mTOR. SGK1 is a powerful stimulator of Na+/K+-ATPase, carriers (e.g. the Na+,K+,2Cl- cotransporter NKCC, the NaCl cotransporter NCC, the Na+/H+ exchanger NHE3, and the Na+ coupled glucose transporter SGLT1), and ion channels (e.g. the epithelial Na+ channel ENaC, the Ca2+ release activated Ca2+ channel Orai1 with its stimulator STIM1, and diverse K+ channels). SGK1 further participates in the regulation of the transcription factors nuclear factor kappa-B NFκB, p53, cAMP responsive element binding protein (CREB), activator protein-1, and forkhead transcription factor FKHR-L1 (FOXO3a). Enhanced SGK1 activity fosters the development of hypertension, obesity, diabetes, thrombosis, stroke, inflammation including inflammatory bowel disease and autoimmune disease, cardiac fibrosis, proteinuria, renal failure as well as tumor growth. The present brief review makes the case that suboptimal fluid intake in the common population may enhance vasopressin and glucocorticoid levels thus up-regulating SGK1 expression and favouring the development of SGK1 related pathologies.